Restorasi Estetik dengan Strip Crown pada Gigi Anterior Desidui (Laporan Kasus): Aesthetic Restoration with Strip Crown for Anterior Primary Teeth (Case Report) - Nendika Dyah Ayu Murika Sari; Putri Kusuma Wardani Mahendra (Jurnal Surya Medika (JSM), 2023)
Background: Anterior dental caries affect masticatory function and aesthetics. The most popular type of aesthetic crown for the restoration of deciduous incisors is the strip crown. Purpose: to report the case of restoration of an aesthetic restoration with a strip crown on anterior primary teeth. Case: A 5.5-year-old boy comes with his mother with complaints of tooth decay. He never hurts and has never been traumatized. A clinical examination revealed that the teeth 52, 51, 61, and 62 had extensive dentinal caries in all parts. Diagnosis based on ICDAS is caries class 5. Case Management: The teeth were subjected to crown-strip restoration in two visits. The first visit was for teeth 51 and 61, and the second visit was for teeth 52 and 62. The teeth were cleaned with carious tissue, lining, and application of flowable composite resin with strip crown, polishing, and finishing. Conclusion: Strip crown restoration can be an alternative choice for primary anterior teeth where caries extends throughout the crown and improves aesthetic results.